Characterisation of the complete mitochondrial genome of the Jinchuan Yak (Bos grunniens) - Bao, Pengjia (Mitochondrial DNA B Resour, 2019)
Jinchuan yak was a newly discovered yak breed, not only possesses a large proportion of multi-ribs but also exhibits many good characteristics. However, there is limited information about its overall genetic structure. In this study, we assembled the mitochondrial genome for Jinchuan yak (Bos grunniens), the results show that the mitochondrial genome is 16,324bp long with an A + T-biased base composition (61.0% A + T) and harbours the typical set of 37 mitochondrial genes and 1 non-coding control region. The PCGs start with the typical ATA or ATG codons and are terminated with TAA, TAG or the incomplete stop codon T. Phylogenetic analysis suggests that Jinchuan yak is most closely related to Datong yak and Sunan yak.